Internalisasi Nilai-Nilai Pendidikan Akhlak dalam Dasa Dharma Pramuka di SMKN 1 Tonjong Brebes: Internalization of Moral Education Values in Dasa Dharma Scouting at SMKN 1 Tonjong Brebes - Intan Pandini Gunawan, Yosi; Ashila Nur Aqilah, Salwa (CV. Kalimasada Group, 2023)
The morality crisis that is occurring in Indonesia is a serious problem faced by this nation. This can be seen when there are many cases of deviations committed by students. Brawls and promiscuity are examples of the consequences of collapsing moral values, so students need moral education. In scouting, there is education that concentrates on moral values ​​because scouting's moral values ​​come from scouting satya and dharma. So that through scouting activities we can produce students who have good morals. This research aims to find out how the internalization of moral education values ​​in the Dasa Dharma Scouts at SMKN 1 Tonjong Brebes. This research is field research using a descriptive qualitative approach, where data is collected obtained through observation, interviews and documentation. The results of the research show that the internalization of moral education values ​​in the scout dasa dharma at SMKN 1 Tonjong Brebes shows that it has been implemented in every point of the scout dasa dharma.